Dampak Implementasi Sistem Informasi Manajemen terhadap Kualitas Layanan Administrasi Pendidikan: The Impact of Management Information System Implementation on the Quality of Educational Administration Services - Ariatpi, Fina; Ismatullah, Ade (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
Improving the quality of administrative services in educational institutions has become a priority in the current digital era. Management Information Systems (MIS) are implemented as solutions to enhance efficiency, effectiveness, and productivity in managing educational administration. However, several challenges remain, including user dissatisfaction with system usability, accessibility, and responsiveness. This study aims to explore the impact of MIS implementation on the quality of administrative services in education, focusing on user experience and operational efficiency within educational institutions. The research employs a literature review method, involving an in-depth analysis of relevant literature, including journals, books, and research reports. The findings indicate that the success of MIS depends not only on technical aspects but also on the management of human resources, IT infrastructure, and responsive strategies tailored to user needs. These findings are expected to serve as a foundation for educational institutions to formulate more effective MIS management strategies, thereby delivering high-quality administrative services.